Edukasi Kesehatan Kulit Perempuan Indonesia melalui Media Sosial pada Akun Instagram @hi.flawless - Claudia, Benedicta Yovi; Marta, Rustono Farady; Rewindinar, Rewindinar (Jurnal Komunikasi Profesional, 2021)
Content marketing has become an essential part of any social media marketing strategy. However, the effectiveness of a content marketing strategy through social media will be determined by its alignment with the prevailing communication model. This study aims to analyze the communication model that takes place in the marketing of educational content regarding the health of Indonesian women's skin on Instagram @ hi.flawless and determine the effectiveness of the content marketing based on the communication model that occurs. This study uses a qualitative approach with a netnographic method. Data collection methods are through observation and interviews, while data analysis techniques use data reduction, data presentation, and drawing conclusions analysis methods. This research shows that the communication model that occurs is Schramm's interactional communication model which can then be further developed into a multistep non-linear communication model and advanced web communication. The use of Indonesian women's skin health education as content for marketing on Instagram @ hi.flawless is known to be in line with the prevailing and effective communication model to be implemented, seen from the relatively high level of consumer involvement and the increase in sales that have occurred. Keywords: communication model, content marketing, education, social media